Current issues of formation and preservation of documents of creative process of scientists in personal archival fonds - Yemchuk Oksana (Рукописна та книжкова спадщина України)

(untitled)
The purpose of the work is to analyze the current issues of formation and preservation of documents of the creative process of scientists in personal archival fonds on the basis of normative and methodical documents regulating the work with personal fonds of scientists of the National Academy of Sciences of Ukraine, as well as a review of foreign experience. The research methodology is based on the principles of historicism, scientificity, and systematicity. With the results of the interdisciplinary approach, the methods of terminological and historiographic analysis, criticism of historical sources were used. Scientific novelty. Based on the analysis of normative and methodical documents relevant to the article, examples of foreign experience, directions for further work on the formation and preservation of documents of the creative process of scientists in modern conditions of digital technologies are determined. Conclusions. The processes of formation and preservation of personal fonds are generally regulated by a number of regulatory and methodological documents, however, in order topreserve the documents of the creative process of scientists in the conditions of digital technologies, there is a need for appropriate theoretical and methodological developments, newpractical instructions prepared on the basis of interdisciplinary approaches. Some types of creative documents require a more precise terminological definition and agreement on their storage terms. The effective formation and preservation of personal archive fonds with documents of the creative process of scientists depends on the establishment of effective relations between archivists and scientists on the basis of high-quality methodical support and adaptation of the best foreign experience.